Washington View: Education and presidential politics. (March 2020) - Ferguson, Maria
Education issues often get attention during presidential elections, even though education is primarily a state and local issue. Maria Ferguson looks at how the 2020 presidential campaigns have dealt with such education issues as the plight of teachers and the value of charter schools. In many instances, these issues have been controversial, but they don't generally stay in the spotlight for the entire campaign season .